EMPIRICAL ANALYSIS FOR REGULATORY FRAMEWORK OF E-COMMERCE - Kaur, Amandeep (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
World is changing at a remarkable pace and so does the world of marketing. The limited options to communicate with the target audience have been widening. Even the technology has profoundly changed the way consumer process communication. In the last few years the internet has played a major role in many fields of economy as it is commonly defined as a global media. The internet has been largely used in commerce and management. Electronic commerce, commonly written as e-commerce or E-Commerce, is the trading or facilitation of trading in products or services using computer networks, such as the Internet. The rapid adoption of the Internet as a commercial medium has caused firms to experiment with the innovative ways of commerce thus changing the pattern of commerce strategies. The primarily motive of the study was to investigate the awareness level of respondents regarding the regulatory framework of E-Commerce. The present study was exploratory research by the means of primary data analysis wherein an attempt was made to identify the awareness level of respondents regarding regulatory framework of e-commerce with the help of self structured questionnaire. The questionnaire was based on the five point Likert scale ranging from not at all aware to completely aware and the convenience sampling was used to collect the data from respondents (250) residence of Punjab and Union Territory of Chandigarh. Further, chi square technique was used to test the null hypothesis as whether there was significant relationship between regulatory framework, gender and monthly income attributes. It was observed that female respondents were more aware as compared to male respondents regarding the regulatory framework of e-commerce. On the basis of monthly income attribute, 15000-30000 income group’s respondents were not aware regarding the regulatory framework of e-commerce but in the next income group ranging from 50000-75000 were aware about the regulatory framework of the e-commerce.